Why do smokers diagnosed with COPD not quit smoking? - a qualitative study - Eklund, Britt-Marie; Nilsson, Siv; Hedman, Linnea; Lindberg, Inger (Tobacco Induced Diseases, 2012)
Chronic Obstructive Pulmonary Disease (COPD) is currently one of the most widespread chronic lung diseases and a growing cause of suffering and mortality worldwide. It is predicted to become the third leading cause of death in the near future. Smoking is the most important risk factor, and about 50% of smokers develop COPD. Smoking cessation is the most important way to improve prognosis. The aim of the study was to describe difficulties of smoking cessation experienced by individuals with COPD who are unable to stop smoking. MethodsTen smokers (five women) with COPD, GOLD stage II, participated in semi-structured interviews in 2010. The data were analyzed using qualitative content analysis. The participants were recruited from the Obstructive Lung Disease in Northern Sweden (OLIN) studies. ResultsThe participants lives were governed by a lifelong smoking habit that was difficult to break although they had knowledge about the harmful effects and the consequences of COPD. The participants described incidents in their lives as reasons for never finding the time to quit smoking. Demands to quit smoking from other people could lead to continued smoking or get them started again after cessation as they did not want to be patronized. They wanted to receive support from relatives and care providers but they wanted to make the decision to quit on their own. ConclusionFor successful smoking cessation, it is important to understand the difficulties smokers are experiencing that influence their efforts to quit smoking. To achieve a successful lasting smoking cessation it might be more effective to first ensure that the smoker has the right internal motivation to make the decision to quit, then assist with smoking cessation. Godkänd; 2012; 20121128 (andbra); Full text license: CC BY 2.0